Corporate Governance and the Goal of the Firm: In Defense of Shareholder Wealth Maximization. Issue 4 (November 2016) - Denis, Diane
Abstract: This essay is based on my keynote address at the 2016 annual meeting of the Eastern Finance Association. I propose that misunderstandings about the traditional model of corporate governance, with its emphasis on shareholder wealth maximization, contribute to negative societal attitudes about corporations. I discuss the implications of shareholder wealth maximization for other corporate stakeholders, the dangers of deviating from shareholder wealth maximization, and the roles that the media and the government play in the governance of corporations.